Analysis of Network Structures in Thiol-Ene UV Curing System Using Reworkable Resins - Okamura, Haruyuki (Polymers (Basel), 2018)
An analysis of the network structures in thiol-ene UV curing resins was carried out using reworkable resins composed of di(meth)acrylate monomers having tertiary ester linkages. The effect of the functionality of the thiols, the functional ratio of the thiol and ene functions, their conversions and curing atmosphere on the chain lengths was discussed. A mixture of (meth)acrylates, thiol compounds, a photoradical initiator, and a photoacid generator was cured by irradiation at 365 nm. The cured samples were degraded by heating after irradiation at 254 nm. Size exclusion chromatography (SEC) and (1)H NMR analyses of the degraded samples were carried out after the methylation. The crosslinking conditions strongly affected the network structures. The degraded samples have molecular weights between 250 and 2700. The molecular weights of the degraded resins increased with the functionality of the thiol compounds. The chain length dependence suggests that thiol compounds with a high functionality have a low reactivity due to steric hindrance. The chain lengths of the degraded networks were nearly proportional to the concentration of the (meth)acrylate monomers. The addition of reactive diluents enhanced the reactivity and increased the chain length.